2021
DOI: 10.18291/njwls.123167
|View full text |Cite
|
Sign up to set email alerts
|

Career Stability in 14 Finnish Industrial Employee Cohorts in 1988–2015

Abstract: It is often argued that global competition and technological development have made industrial jobs more unstable. In this article, we ask how career stability has evolved in the Finnish forest, metal, and chemical industries, comparing 14 cohorts (age groups) by gender and educational level. We focus on industrial employees born in 1958–1971 and compare their career stability at ages 30–44 using Statistics Finland’s linked employer-employee data from 1988 to 2015 and an application of sequence analysis. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…For about half of the sample (especially women), stability and linearity were confirmed because these groups worked in the same or similar occupations for more than 30 years. These results are consistent with patterns of stability found in other European contexts (Van Winkle and Fasang, 2017;Ojala et al, 2020). Super (1957; called this career process establishing and maintaining one's occupation and position.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For about half of the sample (especially women), stability and linearity were confirmed because these groups worked in the same or similar occupations for more than 30 years. These results are consistent with patterns of stability found in other European contexts (Van Winkle and Fasang, 2017;Ojala et al, 2020). Super (1957; called this career process establishing and maintaining one's occupation and position.…”
Section: Discussionsupporting
confidence: 92%
“…In most studies, sequences and patterns of different activities or roles (education, employment, unemployment, family) and their extent (full-time, part-time and so on) were analysed using SA. Especially in the European context, several studies showed a remarkable stability in career trajectories (Stawarz, 2018;Ojala et al, 2020). In a study of the employment trajectories on men and women from age 15 to 45 born between 1918 and 1963, there was relatively little change throughout birth cohorts compared to those of 14 European countries (Van Winkle and Fasang, 2017).…”
Section: Occupational Career Patternsmentioning
confidence: 99%